Functional and Structural Brain Damage in Friedreich's Ataxia - Vavla, Marinela; Arrigoni, Filippo; Nordio, Andrea; De Luca, Alberto; Pizzighello, Silvia; Petacchi, Elisa; Paparella, Gabriella; D'Angelo, Maria Grazia; Brighina, Erika; Russo, Emanuela; Fantin, Marianna; Colombo, Paola; et al. (Frontiers in Neurology, 2018)
Friedreich's ataxia (FRDA) is a rare hereditary neurodegenerative disorder caused by a GAA repeat expansion in the FXN gene. There is still no cure and no quantitative biomarkers to show any reliable correlations with progression rate and disease severity. Investigation of functional and structural alterations characterizing white matter (WM) and gray matter (GM) in FRDA could be useful to monitor progression and response to treatment. Here we report results of a multimodal cross-sectional MRI study of FRDA including Voxel-Based Morphometry (VBM), diffusion-tensor imaging (DTI), fMRI and a correlation analysis between MRI measures and clinical severity scores. Twenty-one early-onset molecularly-defined FRDA patients and 18 age-matched healthy controls (HCs) were imaged at 3T. All patients underwent a complete clinical cognitive and neurological assessment with the SARA, ICARS and the neurological section of FARS. VBM analysis showed GM volume reduction in FRDA versus HCs in the following areas: bilateral reduction of GM volume in lobule V, VI, VIII (L>R), crus of cerebellum, in the posterior lobe of the vermis, in both the flocculi and in the L tonsil Voxel-wise DTI analysis showed a diffuse fractional anisotropy (FA) reduction and mean, radial, axial diffusivity (MD, RD, AD) increase in both infratentorial and supratentorial WM. The ROI-based analysis confirmed the results showing same DTI metrics impairment in cortico-spinal-tracts, forceps major, corpus callosum, posterior thalamic radiations, cerebellar penduncles and increased AD in superior and middle cerebellar peduncles. The WM findings correlated with age at onset (AAO) in infra- and supratentorial areas, GAAsr and disease severity in SCP, forceps and fornix. The intragroup analysis of fMRI data from right-handed 14 FRDA and 15 HCs showed similar findings in both groups, including activation in M1, insula and superior cerebellar hemisphere (lobules V-VIII). Significant differences emerged only during the movement of the non-dominant hand (left-hand), with HCs showing a stronger activation in the L superior cerebellar hemisphere. Significant correlations were found between AAO and the fMRI activation in cerebellar anterior and posterior lobes, insula and temporal lobe. MRI metrics correlated to clinical data and may prove to be useful paraclinical disease markers, withstanding further validation in a longitudinal study.